Sphingosine‐1‐phosphate induces Ca2+ signaling and CXCL1 release via TRPC6 channel in astrocytes. Issue 6 (16th March 2017) - Shirakawa, Hisashi; Katsumoto, Rumi; Iida, Shota; Miyake, Takahito; Higuchi, Takuya; Nagashima, Takuya; Nagayasu, Kazuki; Nakagawa, Takayuki; Kaneko, Shuji
Abstract: A biologically active lipid, sphingosine‐1‐phosphate (S1P) is highly abundant in blood, and plays an important role in regulating the growth, survival, and migration of many cells. Binding of the endogenous ligand S1P results in activation of various signaling pathways via G protein‐coupled receptors, some of which generates Ca 2+ mobilization. In astrocytes, S1P is reported to evoke Ca 2+ signaling, proliferation, and migration; however, the precise mechanisms underlying such responses in astrocytes remain to be elucidated. Transient receptor potential canonical (TRPC) channels are Ca 2+ ‐permeable cation channels expressed in astrocytes and involved in Ca 2+ influx after receptor stimulation. In this study, we investigated the involvement of TRPC channels in S1P‐induced cellular responses. In Ca 2+ imaging experiments, S1P at 1 μM elicited a transient increase in intracellular Ca 2+ in astrocytes, followed by sustained elevation. The sustained Ca 2+ response was markedly suppressed by S1P2 receptor antagonist JTE013, S1P3 receptor antagonist CAY10444, or non‐selective TRPC channel inhibitor Pyr2. Additionally, S1P increased chemokine CXCL1 mRNA expression and release, which were suppressed by TRPC inhibitor, inhibition of Ca 2+ mobilization, MAPK pathway inhibitors, or knockdown of the TRPC channel isoform TRPC6. Taken together, these results demonstrate that S1P induces Ca 2+ signaling in astrocytes via Gq ‐coupled receptors S1P2 and S1P3, followed by Ca 2+ influx through TRPC6 that could activate MAPK signaling, which leads to increased secretion of the proinflammatory or neuroprotective chemokine CXCL1. Main Points: Activation of Gq ‐coupled receptors S1P2 and S1P3 by S1P triggers Ca 2+ influx through TRPC6, which results in MAPK activation and increased secretion of the proinflammatory or neuroprotective chemokine CXCL1 in astrocyte in vitro .